2018
DOI: 10.1002/14651858.cd003869.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Whole brain radiotherapy for the treatment of newly diagnosed multiple brain metastases

Abstract: None of the trials with altered higher biological WBRT dose-fractionation schemes reported benefit for OS, NFI, or symptom control compared with standard care. However, OS and NFI were worse for lower biological WBRT dose-fractionation schemes than for standard dose schedules.The addition of WBRT to radiosurgery improved local and distant brain control in selected people with brain metastases, but data show worse neurocognitive outcomes and no differences in OS.Selected people with multiple brain metastases fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(105 citation statements)
references
References 77 publications
2
90
0
3
Order By: Relevance
“…These subgroups fall broadly in line with both the RPA 8 and disease-specific Graded Prognostic Assessments (ds-GPA), 10 both developed by the Radiation Therapy Oncology Group (RTOG). Since the RPA prognostic classes were described, the oncology community has broadly concluded that those patients who fell into the better RPA classes 1 and 2 required WBRT, whereas those within the poorest prognostic group (class 3, median survival 2·3 months) did not require WBRT, despite the absence of a solid evidence base to support this approach 16 . Patients who fell within RPA class 3 were thus excluded from any subsequent brain metastases trials that involved radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These subgroups fall broadly in line with both the RPA 8 and disease-specific Graded Prognostic Assessments (ds-GPA), 10 both developed by the Radiation Therapy Oncology Group (RTOG). Since the RPA prognostic classes were described, the oncology community has broadly concluded that those patients who fell into the better RPA classes 1 and 2 required WBRT, whereas those within the poorest prognostic group (class 3, median survival 2·3 months) did not require WBRT, despite the absence of a solid evidence base to support this approach 16 . Patients who fell within RPA class 3 were thus excluded from any subsequent brain metastases trials that involved radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, a Cochrane review 16 in 2012 only identified one randomised controlled trial (RCT), done by the Eastern Cooperative Oncology Group (ECOG) and published in 1971, specifically addressing the efficacy of supportive care plus WBRT compared with supportive care alone. This study randomised only 48 patients with multiple primary tumour sites (30 with lung cancer; the number with NSCLC as opposed to small-cell lung cancer was not specified) to prednisone only or prednisone plus WBRT 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Current treatment algorithms recommend surgery or SRS for oligometastatic and symptomatic BM151617. For patients with multiple BM, WBRT remains the standard of care18. However, WBRT is associated with potential long-term neurocognitive toxicities, which are concerning when considering prolonging the life of patients with BM and EGFR mutations.…”
mentioning
confidence: 99%
“…There are numerous controversies in the literature about the role of WBRT as a treatment adjuvant to SRS [8, 35, 4548, 5456]. In retrospective studies Sneed et al and Hu et al did not find any positive effect of adjuvant WBRT on survival [5456].…”
Section: Radiotherapymentioning
confidence: 99%
“…In retrospective studies Sneed et al and Hu et al did not find any positive effect of adjuvant WBRT on survival [5456]. In three controlled clinical studies, the efficiency of SRS versus SRS + WBRT was evaluated [45]. Studies by Aoyama et al [47] and Kochera et al [46] did not show any difference in patients’ survival, but addition of WBRT statistically significantly improved local and distant (brain areas outside the SRS volume) control.…”
Section: Radiotherapymentioning
confidence: 99%